Modelling analysis for vibration energy harvesting excited by low-speed automobile tires - Yunshun ZHANG; Rencheng ZHENG; Kenji EJIRI; Dongxu SU; Kimihiko NAKANO (Nihon Kikai Gakkai ronbunshu, 2016)
This study reports a vibrational energy harvesting system applied for low-speed vehicle tires on the asphalt road. The systematic model was analyzed under the measured road noise, in which a cantilever beam pasted piezoelectric film and magnets with the same polarity are fabricated as a nonlinear bistable vibrating system, when vehicle travels on the asphalt road at the different speeds of 10-20 km/h. By the theoretical investigation and simulation study, in the case of combination of a periodic modulating force which is autonomously offered from the gravitational effect of the magnetic end mass with the tire rotation and a vertical road noise excitation which is produced by the interaction of the tire and road surface, it can be observed that the potential becomes practically realizable to stimulate stochastic resonance, which can apparently enhance energy harvesting at the angular velocity of 14.4 rad/s. With consideration of the theory of stochastic resonance in this research, the vibrating responses become significantly strong to generate more available energy, where the energy captured from not only the road ambient, but also its gravitational acting. Hence, the proposed energy harvester model is capable of being utilized under the vehicle tire rotation circumstances. Furthermore, the suggested application for this harvester is to provide electrical power for tire pressure sensors.